Experimental Study on the Durability of Fly Ash-Based Filling Paste in Environments with Different Concentrations of Sulfates - Boqiang Cui; Yin Liu; Hao Guo; Zhanxin Liu; Yao Lu (Advances in Materials Science and Engineering)
In order to study the effects of different concentrations of sulfate on the strength of fly ash-based coal mine filling paste, using variable control, mechanical analysis, and other means, the changes in the uniaxial compressive strengths of filling paste blocks soaked in different concentrations of sodium sulfate solution for different durations are studied, and their stress-strain curves are discussed. The hydrated products of each block are analyzed at different stages by XRD, and the results indicate that different concentrations of sodium sulfate solution have different effects on the strength of the filling paste after soaking for different durations. A sodium sulfate solution with a concentration of 5% had an activator effect on the fly ash-based filling paste and enhanced the strength of the filling paste. A sodium sulfate solution with a concentration of 10% and 15% increased the early strength of the paste test block faster, but after 60 d, the strength decreased. The stress-strain curves for these blocks show that the elastic moduli of the filling paste test blocks change irregularly, and it was found that with the increase in soaking time, the blocks soaked in the 10% and 15% sodium sulfate solutions developed fissures in the later stage that adversely affected the strength of the filling paste. The XRD results show that the filling paste test block hydration products are hydrated calcium silicate (C-S-H) based and that ettringite (AFt), beneficial to strength of the filling paste in proper quantities, appeared in the main product of the filling paste test blocks that were soaked in the sodium sulfate solution. With the increase in the concentration of the sodium sulfate solution, the AFt is generated in larger quantities, and gypsum crystals begin to appear, which is not conducive to the filling paste block strength.